ANALISIS PEMECAHAN MASALAH SISWA SMP NEGERI 7 PALU DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SPLDV DITINJAU DARI ADVERSITY QUOTIENT - Meri Safitri M. Rasul; Nurhayadi, Nurhayadi; Ismaimuza, Dasa (Universitas Tadulako, 2022)
The purpose of this research is to describe of problem solving of Students Class VIII SMP Negeri 7 Palu in Solving the Narrative Test of Linear Equations in Two Variables in terms of Adversity Quotient (AQ). This type of research was qualitative. The subject in this research was three student class VIII SMP Negeri 7 Palu in even semester of the academic year of 2021/2022 which consisted of student each of the climber type, the camper type, and the quitter type. Data about students’ problem solving were collected by written tests and interviews, while data about students’ adversity quotient were obtained by giving ARP questionnaires. The results of this research show that (1) problem solving climber type students are able to carry out the stage of understanding the problem, devising a plan, carrying out the plan of solving and looking back, (2) problem solving camper type students are able to carry out the stage of understanding the problem, devising a plan, and carrying out the plan of solving, (3) problem solving quitter type students are able to carry out the stage of understanding the problem and devising a plan.